Highly efficient folding of multi‐disulfide proteins in superoxidizing Escherichia coli cytoplasm. Issue 12 (5th August 2014) - Zhang, Wenyao; Zheng, Wenyun; Mao, Miaowei; Yang, Yi
ABSTRACT In this study, we monitored the thiol–disulfide redox potential of different Escherichia coli strains using redox‐sensitive variants of green fluorescent protein. The cells with extreme oxidizing cytoplasm were generated by introducing a highly efficient disulfide relay system. The developed cells have exceptionally efficient de novo disulfide bond formation and significantly improve the oxidative folding of the client multi‐disulfide proteins. Superoxidizing E. coli strain provides an effective method for the high‐level production of recombinant disulfide‐containing proteins. Biotechnol. Bioeng. 2014;111: 2520–2527. © 2014 Wiley Periodicals, Inc.